The Role Of The Cultural Code In Studying The Psychology Of Social Creativity (Eurasian Journal of Media and Communications, 2024)
The article examines the concept of "cultural code", its application in the fields of linguistics, anthropology, social psychology and cultural studies, and also reveals the role of cultural code in management and marketing activities.